Climate extremes and the carbon cycle - Reichstein, Markus; Bahn, Michael; Ciais, Philippe; Frank, Dorothea; Mahecha, Miguel D.; Seneviratne, Sonia I.; Zscheischler, Jakob; Beer, Christian; Buchmann, Nina; Frank, David C.; Papale, Dario; Rammig, Anja; et al. (Nature (London), 2013)
The effects of climate extremes such as droughts or storms on the carbon cycle of ecosystems are investigated; such extremes can decrease regional carbon stocks. Carbon budget changes caused by climate extremes Recent studies indicate that the extreme climate events — such as heatwaves, droughts and storms — can partially offset carbon sinks or even cause net losses in carbon stocks. This Perspective article investigates the effect of climate extremes on the carbon cycle of terrestrial ecosystems and concludes that climate extremes have the potential to override the sink effects of gradual warming, contributing to carbon loss from accumulated stocks. The terrestrial biosphere is a key component of the global carbon cycle and its carbon balance is strongly influenced by climate. Continuing environmental changes are thought to increase global terrestrial carbon uptake. But evidence is mounting that climate extremes such as droughts or storms can lead to a decrease in regional ecosystem carbon stocks and therefore have the potential to negate an expected increase in terrestrial carbon uptake. Here we explore the mechanisms and impacts of climate extremes on the terrestrial carbon cycle, and propose a pathway to improve our understanding of present and future impacts of climate extremes on the terrestrial carbon budget.